Simultaneous Determination of Na+, K+, Ca2+, Mg2+ and Cl− in Unstimulated and Stimulated Human Saliva Using All Solid State Multisensor Platform. Issue 10 (29th June 2017) - Urbanowicz, Marcin; Jasiński, Artur; Jasińska, Małgorzata; Drucis, Kamil; Ekman, Marcin; Szarmach, Arkadiusz; Suchodolski, Rafał; Pomećko, Radosław; Bocheńska, Maria
Abstract: Human saliva is one of the body fluids which collection method is relatively simple and non‐invasive. The article is dedicated to assess concentration (activity) of Na +, K +, Ca 2+, Mg 2+ and Cl − in fresh, unstimulated or stimulated human saliva samples using single solid contact ion‐selective electrodes with conventional reference electrode and self‐made multisensor platform (MP) equipped with ion‐selective membranes for Na +, K +, Ca 2+, Mg 2+ and Cl − and reference electrode made in solid state technology, based on dispersed KCl in the polymer. Both kind of electrodes, single ISE and miniaturized electrodes in multisensor platform (ISE‐MP) were made of glassy carbon. The electrode surfaces have been modified by conductive polymer (PEDOT) layer deposition; with the exception of Cl − electrode, in which conducting polymer was not applied. Potentiometric measurements were used to compare the changes of the ionic composition in various samples of saliva. Abstract :